2015
DOI: 10.5721/eujrs20154828
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of iron and steelwork by-products using close range hyperspectral imaging: A case study in Thuringia, Germany

Abstract: This paper presents the first use of close range terrestrial hyperspectral imaging to explore by-products from the iron and steel industry at a dump site cross section, using established mapping approaches in geological remote sensing. Laboratory reflectance measurements, X-Ray diffraction and chemical analysis provided a benchmark for the imaging results. In addition, terrestrial laser scanning was applied to create a high resolution 3D model of the studied section, for hyperspectral image and classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A study with the purpose to map steelworks and iron byproducts identified jarosite and other iron minerals [31], achieving promising results with a hyperspectral mapping approach and endmembers deviated from image scenes in combination with geochemical validation.…”
Section: Study Areamentioning
confidence: 99%
“…A study with the purpose to map steelworks and iron byproducts identified jarosite and other iron minerals [31], achieving promising results with a hyperspectral mapping approach and endmembers deviated from image scenes in combination with geochemical validation.…”
Section: Study Areamentioning
confidence: 99%
“…The utilization of CS in iron ore sintering can replace parts of the iron ore and the flux, which is beneficial to energy saving and consumption reduction [27,[42][43][44]. It has been reported that the utilization of CS in iron ore sintering for ironmaking is the most effective recovery method due to the high production of sinter [45].…”
Section: Iron Ore Sinteringmentioning
confidence: 99%
“…Environmental services include applications for sustainability, characterization of green space, air quality measurement, land use planning and ground cover, bioassays, and waste remediation and recycling. Asset management includes applications in transportation systems, building recognition, and infrastructure appraisal [8][9][10][11][12][13][14]…”
Section: A Available Instruments For Sensingmentioning
confidence: 99%